A transcriptomic-guided strategy used in identification of a wheat rust pathogen target and modification of the target enhanced host resistance to rust pathogens - Nyamesorto, Bernard; Zhang, Hongtao; Rouse, Matthew; Wang, Meinan; Chen, Xianming; Huang, Li (Frontiers in Plant Science, 2022)
Transcriptional reprogramming is an essential feature of plant immunity and is governed by transcription factors (TFs) and co-regulatory proteins associated with discrete transcriptional complexes. On the other hand, effector proteins from pathogens have been shown to hijack these vast repertoires of plant TFs. Our current knowledge of host genes' role (including TFs) involved in pathogen colonization is based on research employing model plants such as Arabidopsis and rice with minimal efforts in wheat rust interactions. In this study, we begun the research by identifying wheat genes that benefit rust pathogens during infection and editing those genes to provide wheat with passive resistance to rust. We identified the wheat MYC4 transcription factor (TF) located on chromosome 1B (TaMYC4-1B) as a rust pathogen target. The gene was upregulated only in susceptible lines in the presence of the pathogens. Down-regulation of TaMYC4-1B using barley stripe mosaic virus-induced gene silencing (BSMV-VIGS) in the susceptible cultivar Chinese Spring enhanced its resistance to the stem rust pathogen. Knockout of the TaMYC4-1BL in Cadenza rendered new resistance to races of stem, leaf, and stripe rust pathogens. We developed new germplasm in wheat via modifications of the wheat TaMYC4 -1BL transcription factor.